David Ricardo – recognized leader in classical political economy (to the 250th anniversary of his birth) - Chyrak, Iryna (Herald of Economics, 2022)
Introduction. David Ricardo is a very prominent figure in the history of economic thought. He is a recognized leader in classical political economy and a reputable financier in both Britain and Europe in the first half of the XIX century. He is rightly considered one of the creators of the labor theory of value, he has brought it to its logical conclusion. The scientist made a significant contribution to the development of a scientific method for studying economic phenomena.Purpose of the research is to generalize the economic views of a prominent scientist on economic phenomena and processes, the action of economic laws that ensure the balance of a market economy and the basic principles of economic liberalism; analyze the Ricardo’s views on the laws of social wealth distribution between three classes of society and the impact of the existing distribution of income on the growth of wealth.Methods. The methodological basis of the study are such general scientific methods as analysis, synthesis, induction and deduction, which were used to assess the views, conclusions and recommendations of the scientist to ensure market equilibrium and increase the material wealth of society; historical – to understand the essence of the evolution of existing views on the labor theory of value, the theory of money and land rent; combining the abstract method with quantitative analysis to determine the quantitative characteristics of economic phenomena; positive and normative – to study the main and distinctive features in the views of representatives of classical political economy.Results. It has been researched the David Ricardo’s scientific work and it has been established that he was a prominent representative of classical political economy, a follower and at the same time an opponent of certain theoretical positions of Adam Smith. It was found that the most important ideas of economic theory have been reflected in his labor theory of value, the theory of capital and money, the theory of income distribution, tax theory and the theory of comparative advantage in international trade. It was established that the scientist had made a significant contribution to the development of the scientific method of research, in particular, by introducing the method of convergence from the abstract to the concrete and widespread use of the method of scientific deduction. According to the scientist, the subject of political economy should be the study of the laws of distribution of income between classes of society in the form of rents, profits and wages. D. Ricardo made a significant contribution to the justification of free trade policy in the international sphere, the importance and profitability of foreign trade for countries.Discussion. The prospect for further research is a deeper and more detailed analysis of the methods used by the scientist in the study of economic phenomena and processes. This will allow assessing the Ricardo’s contribution to the formation and development of economics more objective.